Rodinný dům s cukrárnou - Šubrtová, Michaela (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Předmětem bakalářské práce je zpracování stavebně technické části projektové dokumentace pro realizaci novostavby rodinného domu s cukrárnou v obci Květnice. Objekt je určen pro pětičlennou rodinu. Navržený dům má dvě nadzemní podlaží. Je navržen jako samostatně stojící na rovinatém terénu. Nosný systém objektu je navržen ze systému Porotherm. Střecha nad cukrárnou je plochá, nad RD je řešena novodobým vazníkovým krovem. Na střešní krytinu je použit systém Bramac.

The subject of this bachelor´s thesis is processing of building – technical part of project documentation for realization of new building of family house and confectionery in village Květnice. The building is designed for a family of five. The proposed building has two floors. Is designed as a standalone house on a flat terrain. The supporting system of the building are made up by system Porotherm. The roof is flat over the confectionary, over RD is solved by modern truss. The roofing system is used Bramac.
Detached House with Confectionery
Keywords: Projektová dokumentace; rodinný dům; cukrárna; systém Porotherm; valbová střecha; plochá střecha.; Project documentation; detached house; confectionery; system Porotherm; hip roof; flat roof.